2002
DOI: 10.1034/j.1600-0412.2002.810104.x
|View full text |Cite
|
Sign up to set email alerts
|

Substandard factors in perinatal care in The Netherlands:

Abstract: Perinatal deaths might be partly preventable in The Netherlands. There is no evidence that the frequency of substandard factors is related to specific aspects of the perinatal care system in The Netherlands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…The incidence of substandard care factors is in agreement with other studies on stillbirths. However, in these studies, term stillbirths were not analyzed separately (9–11). The most common substandard care factor was inadequate management of suspected growth restriction and maternal hypertension or a combination of these two.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of substandard care factors is in agreement with other studies on stillbirths. However, in these studies, term stillbirths were not analyzed separately (9–11). The most common substandard care factor was inadequate management of suspected growth restriction and maternal hypertension or a combination of these two.…”
Section: Discussionmentioning
confidence: 99%
“…The cornerstone of the Dutch obstetric system is the division of pregnant women into low and high(er) risk with respectively care in primary care by a midwife and secondary care by an obstetrician (9–12). There were 37 stillbirths in primary care and 22 in secondary care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on the quality of perinatal care showed no differences in scores of substandard care between midwives and gynaecologists and home and hospital deliveries. 13 A study on vaccination coverage found a lower coverage of ethnic minority children, but these were predominantly ethnic minority children born abroad, 14 which indicates no large ethnic differences in access to child health centres. On the other hand, differences in the utilisation of care are conceivable, and might increase the risks of infant mortality among ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the transfer rate during delivery is even higher in the Netherlands, the death rate among the transferred was 8.3 per 1,000, a percentage similar to what was found in England (4). One reason might be substandard care: intrapartum/ early neonatal deaths for booked home deliveries were higher (30%) than for hospital births (22%), especially after transfers (44%) (15). The other explanation might be that even a full integration of homebirth practice into a modern health system is not enough to accomplish a safe birth according to modern standards.…”
Section: Ulf Hö Gbergmentioning
confidence: 99%